2022
DOI: 10.1021/acsanm.2c01108
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Dynamic Assembly of Gold Nanoparticles in a Lab-on-Fiber Platform for Surface-Enhanced Raman Scattering Detection

Abstract: As a highly functional platform, lab-on-fiber (LOF) has exhibited amazing potential to be used in ultrasensitive surface-enhanced Raman spectroscopy (SERS) detection. However, the low detection efficiency and high cost of most SERS-based LOF platforms have severely limited their further applications in environmental monitoring, biomedicine, etc. Here, we report a reusable SERS-based LOF platform through a Au-coated optical fiber integrated into a patterned microfluidic chip. With the assistance of laser-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…[40] Moreover, biomolecules auto-fluoresce after absorbing 532 nm to add a fluorescence background in the SERS spectra. [40] Zheng et al [15] have built a lab-on-fiber platform for thermophoretic reversible assembly of cetyltrimethylammonium bromide (CTAB)-capped AuNPs and SERS measurements on R6G and a few environmental pollutant molecules. The platform uses a microfluidic channel integrated with a gold-coated fiber tip and dual-wavelength excitation for AuNP assembling and SERS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] Moreover, biomolecules auto-fluoresce after absorbing 532 nm to add a fluorescence background in the SERS spectra. [40] Zheng et al [15] have built a lab-on-fiber platform for thermophoretic reversible assembly of cetyltrimethylammonium bromide (CTAB)-capped AuNPs and SERS measurements on R6G and a few environmental pollutant molecules. The platform uses a microfluidic channel integrated with a gold-coated fiber tip and dual-wavelength excitation for AuNP assembling and SERS.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Kang et al demonstrated the laser-induced microbubble-assisted reversible assembly of PMNPs for SERS applications detecting rhodamine 6G (R6G) down to 10 −7 m. [14] In recent work, laser-induced thermophoresis on gold-coated fiber tip has been utilized to create a reversible dynamic assembly of gold nanoparticles (AuNPs) for SERS probing. [15] However, the involvement of surfactants in thermophoretic tweezers [15,16] and the high laser power used in microbubble formation can harm the stability of PMNPs and analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the thermophoresis‐based lab‐on‐fiber (LOF) has been developed for ultrasensitive SERS detection of environmental pollutants molecules. [ 159 ] The SERS analysis platform was obtained by integrating the gold thin film (20 nm)‐coated optical fiber into a patterned microfluidic chip. With the assistance of laser (1550 nm)‐induced photothermal effect, the rich hot spots on the gold‐coated fiber were obtained with the power ranging from 50 to 140 mW.…”
Section: Plasmonic Nanostructures‐assisted Optothermal Manipulation O...mentioning
confidence: 99%
“…k) The mechanism of AuNBP assembly on fiber end phase integrated to the microfluidic platform, optical images of l) AuNBP assembly and m) dispersion progress, SERS spectra of environmental pollutants such as n) pyrene and o) thiram solution at various concentration. Reproduced with permission [159]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
“…The combination of SERS and the optical fiber is receiving increasing attention due to its irreplaceable advantages such as good flexibility, robustness, compact structure, microscale, and remote monitoring of hazardous environments. Since Mullen and Carron first demonstrated the original single-mode fiber optic SERS probes in 1991, many improvements have been made in fiber structures and mental nanostructures to achieve higher SERS detection sensitivity and better reproducibility. In the fiber structure, end-face-based fiber optic probes are the most commonly used method, which fixed metal nanostructures directly onto the fiber end face. ,, However, the laser is limited by the propagation of the fiber core and only excites the metal nanoparticles around the fiber core, which reduces the detection sensitivity of the optical fiber SERS sensor.…”
Section: Introductionmentioning
confidence: 99%